2016
DOI: 10.1371/journal.pntd.0004478
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of River Epilepsy in the Orientale Province in the Democratic Republic of the Congo

Abstract: BackgroundAn increased prevalence of epilepsy has been reported in many onchocerciasis endemic areas.ObjectiveTo determine the prevalence and distribution of epilepsy in an onchocerciasis endemic region in the Democratic Republic of the Congo (DRC).Design/MethodsAn epilepsy prevalence study was carried out in 2014, in two localities of the Bas-Uélé district, an onchocerciasis endemic region in the Orientale Province of the DRC. Risk factors for epilepsy were identified using a random effects logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 27 publications
5
35
1
Order By: Relevance
“…In this study, the prevalence of epilepsy increased with decreasing distance to the Mbam River, a breeding site for black flies, and with increasing community microfilariae load . Since then, similar associations have been documented in studies from many other African countries . In particular, a huge case‐control study conducted in several countries of sub‐Saharan Africa found an increased prevalence of epilepsy with onchocerciasis, with an odds ratio of 2.2 (confidence interval [CI] 95%: 1.6–3.2) .…”
Section: Epidemiological Aspectssupporting
confidence: 81%
See 2 more Smart Citations
“…In this study, the prevalence of epilepsy increased with decreasing distance to the Mbam River, a breeding site for black flies, and with increasing community microfilariae load . Since then, similar associations have been documented in studies from many other African countries . In particular, a huge case‐control study conducted in several countries of sub‐Saharan Africa found an increased prevalence of epilepsy with onchocerciasis, with an odds ratio of 2.2 (confidence interval [CI] 95%: 1.6–3.2) .…”
Section: Epidemiological Aspectssupporting
confidence: 81%
“…It is possible that other children, slightly less exposed to Ov and/or exposed later in life, may develop NS (the mean age for developing NS in children in Tumango, in northern Uganda was 7.6 years). Children less exposed to Ov and much later in life may develop epilepsy with minimal or no cognitive impairment and no decrement of growth or sexual development (the mean age of developing tonic‐clonic seizures in the DRC was 11 years).…”
Section: Clinical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most PWE, no obvious other cause could be identified and their psycho-motoric development before the onset of seizures had been normal. The peak onset of epilepsy between the ages of seven and 16 years is a characteristic of OAE as observed elsewhere in Africa (Colebunders et al, 2016b(Colebunders et al, , 2017 when they became heavily infected with O. volvulus at a young age. An argument for this hypothesis is a recent study in South Sudan which showed that the age at onset of nodding seizures was around eight years, while the age of other forms of seizures was around 10 years (Colebunders et al, 2018).…”
Section: Discussionmentioning
confidence: 52%
“…There is, however, accruing evidence from case-control studies associating it with epilepsy [26]. Epilepsy prevalence has been shown to increase near to rivers, which are breeding grounds for the vector, the simulium fly [27,28]. There is also a positive correlation between hyperendemicity of onchocerciasis and high prevalence of epilepsy [29].…”
Section: Onchocerciasismentioning
confidence: 99%